О некоторых социоструктурных последствиях институциональных изменений в украинском обществе - Куценко, О. (Социология: теория, методы, маркетинг, 2000)
The article is dedicated to social effects of the market institutionalization in post-Soviet Ukrainian society. The main ones are transformation of social alienation and formation of a socio-economic threshold of exploitation, as opposed to organiza -tional-bureaucratic exploitation inherent in the Soviet society; social cleavage along the line of social alienation and socio-economic exploitation; symbolical struggle for legitimation of market discourses; formation of a class system of the post-Sovietsociety as a system of the alternative social forces. The author considers the market institutionalization as a compensator reaction of a Soviet type industrial society,which have exhausted its internal resources and is compelled to rush in search of other necessary resources of development. It is considered also in what ways the social cleavage is institutionalizing in class positions and practices.